PENGARUH EKSTRAK KULIT BAWANG PUTIH (Allium sativum Linn) TERHADAP JUMLAH LEUKOSIT dan JUMLAH NEUTROFIL PADA SINUSITIS AKUT BAKTERIAL - shelly tjahyadewi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Background: Acute bacterial sinusitis an inflammatory process and can cause an increase in the number of leukocytes and the number of neutrophils. The content of flavonoids in garlic skin can inhibit the inflammatory process through the process of inhibiting the accumulation of leukocytes and neutrophils in the inflamed area.Objective: This study was conducted to determine the effect of garlic peel extract (Allium sativum Linn) on leukocyte count and neutrophil levels in acute bacterial rhinosinusitis so that it can be used as adjuvant therapy in suppressing the inflammatory process in acute bacterial rhinosinusitis.Methods: This study is an experimental study with post-test only control group design. There were 28 male Sprague Dawley rats divided into 4 groups, including the control group, the group of bacterial acute sinusitis rats without treatment, the group of bacterial acute sinusitis rats treated with amoxicillin and prednisolone antibiotics, and a group of bacterial acute sinusitis rats treated with amoxicillin antibiotics and garlic peel extractResults: Based on the results of the One Way Anova test, the p value < 0.001 showed that there were at least two groups that had a significant difference, namely the effect of giving garlic peel extract (Allium sativum linn) on the number of leukocytes and neutrophil levels.Keywords: sinusitis; Garlic ; Anti-inflammatory;  Leukocytes; Neutrophils